A03 Juvenile Huntington's disease. (29th August 2012) - Quarrell, O
Abstract : Juvenile Huntington's disease is defined as having an onset <20 years. Based on a meta analyisis of 11 post 1980 studies using multiple methods of ascertainment from high income countries (as defined by the World Bank), the proportion of JHD cases was 4.81%, 95% CI 3.31% to 6.58%. These patients are more likely to have bradykinesia and dystonia at an early stage of the illness. A review of the literature on CAG repeat lengths, duration of illness and pharmacological treatment in JHD will be presented. The results of in depth semi-structured interviews with 14 parents from 4 European countries studied using interpretative phenomenological analysis will be reported. Five main themes emerged: early signs of JHD; parental understanding of JHD; living with JHD; knowledge and understanding; and support. These results will be compared with a similar, previously reported study from the UK. The lecture will conclude with proposals for future activity and research.